(3GdJfejI hGdJNWjW GdGbJUGOj (B/s - (3Nda, adjM MSfs ((3YeGf(B: s (3LOGQ ddcJGH GdYGdej(B;(3Yde GdcJH GdMOjK(B, s, 2006)
(3GdJNda GdGbJUGOj GVGaI Gdi fXQjGJ Gdfeh h GdJfejI dGbJUGOjI(B, (3GdJNWjW GdGbJUGOj h eHQQGJg h eJWdHGJg h cPG GfhGY GdJNWjW h fTCJg h eHGOFg h cjajI GYOGO GdNWI h GNjQG GdGOhGJ h GdGSGdjH h GdbQGQGJ GdafjI aj GdJNWjW(B.s
(3eQGLY U(B.433s
Keywords: (3GdJNWjW GdGbJUGOjs; (3GdJfejI GdGbJUGOjIs